Development of a scalable procedure by a discontinuous crossflow DF/UF to obtain a concentrate of chenopodin from a dead-end centrifugal UF at bench scale. (30th May 2020) - Arazo, Migdalia; Jaque, Nestor; Caro, Nelson; Abugoch, Lilian; Tapia, Cristian
Highlights: The first report for the use of DF/UF process for the purification of chenopodin. This process allows for obtaining chenopodin with high purity and protein yield. The complete blockage and cake filtration were the predominant fouling mechanism. The process is easy to handle for scaling up the production of chenopodin. Abstract: The aim of this study was to develop a scalable crossflow diafiltration/ultrafiltration procedure for quinoa 11S globulin purification starting at the bench scale using Ultra15 centrifugal filter devices. The electrophoretic profiles of centrifugal ultrafiltration fractions showed a high heterogeneity in the bands, while crossflow ultrafiltration reduced the phenomena of protein sticking to the membrane, avoiding aggregate formation. In the crossflow protein concentration, flux decline curves were studied according to Hermia's fouling mechanisms and the resistance in a series model. High reversible resistance was related to external mechanisms due to complete blockage of the membrane surface followed by cake formation. The crossflow ultrafiltration was the most efficient technique for obtaining 57 kDa chenopodin isolate with higher processing capacity, purity and protein yield. The diafiltration/ultrafiltration process proved to be adequate and easy to handle to scale up the production of the 11S quinoa globulin.